A finança em John K. Galbraith: estudo sobre o problema do dinheiro e das crises financeiras - Huppes, Gabriel Bonora (2024)
The present investigation is an effort to understand the problem of finance in John K. Galbraith, specifically on the themes of money and financial crises. As for the first theme, it is subdivided into three points: (i.) the notion of money, (ii.) the relationship between currency and the prices of goods and (iii.) the issue of the non-neutrality of money. As for the second theme, it is also subdivided into three points: (i.) the psychology of financial agents, (ii.) the financial business cycle and (iii.) the causes of financial crises. The fundamental objective of this work is to explore Galbraith's historical vision in the highlighted themes and to appreciate the main theoretical notions underlying his work on the problem. Such an effort is justified, above all, by the relative lack of exploration of the problem through bibliographical research. The present efforts can be framed in the modalities of pure and bibliographical research, with some connection to historical research. By investigation method, five stages can be identified: (i.) exploratory contact with the problem and mapping of his works on the problem, (ii.) exploratory examination of secondary bibliography and mapping of bibliographic research, (iii.) collection and gathering of the main citations present in Galbraith's work, (iv.) identification of the main theoretical notions and conceptual analysis and, finally, (v.) complete synthesis of the material gathered. As results of the investigation, it can be highlighted: (i.) the notion of money in Galbraith as a convention instituted by the monetary authority in communion with the community of payment in order to achieve economic convenience and based on scarce material; (ii.) money as a remote and conditioned cause of variations in the price of goods, mediated by the effective pressure of consumption and depending on the satisfaction of the conditions of imperfect liquidity preference and approximately full use of production factors; (iii.) money as univocally non-neutral in its effects; (iv.) the business financial cycle appearing in two major phases, one ascending and the other descending; (v.) speculation in the ascending phase as a proximate cause of financial crises in the descending phase, conditioned by the universality of its practice and the degree of link with the agents' indebtedness; (vi.) the profound deficiency of psychology and human work as a remote and unconditional cause of crises.